Factors Related to Quality of Life and Satisfaction with Nasal Appearance in Patients Treated for Unilateral Cleft Lip and Palate. (July 2013) - Mani, Maria; Reiser, Erika; Andlin-Sobocki, Anna; Skoog, Valdemer; Holmström, Mats
Objective: To identify factors related to quality of life (QoL) and satisfaction with nasal appearance among patients treated for unilateral cleft lip and palate (UCLP). Design: Cross-sectional population study with long-term follow-up. Patients/Settings: All patients with UCLP born between 1960 and 1987, treated at Uppsala University Hospital, were invited (n = 109); 86 (79%) participated. Mean follow-up time was 35 years. Main Outcome Measures: Quality of life was measured with Short Form–36 (SF-36) and analyzed using mental and physical cluster scores (MCS and PCS). Nasal appearance was self-assessed with the "Satisfaction With Appearance" questionnaire and by panel judgment. Multivariate regression analyses explored endogenous factors (age, gender, infancy cleft width, nasal function, nasolabial appearance) and exogenous factors (marital status, number of children, education level, operation method, number of rhinoplasties performed). Results: A larger cleft width in infancy was associated with less satisfaction with nasal appearance as adults. A lower mental health QoL was associated with less satisfaction with nasal appearance. Despite female gender being linked to less satisfaction with nasal appearance, it was associated with higher mental health QoL. Higher resistance during nasal breathing was associated with lower physical health QoL. Conclusions: Gender and infant cleft width may affect QoL and satisfaction with nasal appearance among adults. They are potential predictive factors for satisfaction with nasal appearance and QoL during adulthood. The correlation of nasal function impairment and decreased physical health QoL underlines the importance of treatment of nasal symptoms in these patients.